PENGEMBANGAN MODEL PEMBELAJARAN AKTIF BERBASIS INKUIRI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA CALON GURU - Prayogi, Saiful; Muhali, Muhali; Verawati, Ni Nyoman Sri Putu; Asyari, Muhammad (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
Teachersâ role in teaching and learning processes as well as 21 centuryâs demands, prompted pre-service teachersâ education program to ensure that pre-service teachers will be able to train critical thinking skills to their respective students because critical thinking is an important skill needed by future learners. We developed Inquiry-Based Active Learning Model (ABI) which was implemented to 34 Physics pre-service teachers in one of Teacher Training Institution (LPTK) in Indonesia. The implemented learning model was able to increase critical thinking skills and decreased the number of pre-service teachers previously categorized in a less critical category. In overall, critical thinking skills enhancement after the implementation of ABI learning model is categorized as moderate. We concluded that to some extent, the developed ABI learning model enhanced physics pre-service teachersâ critical thinking skills.